Towards Neuroecosociality: Mental Health in Adversity. (May 2022) - Rose, Nikolas; Birk, Rasmus; Manning, Nick
Social theory has much to gain from taking up the challenges of conceptualizing 'mental health'. Such an approach to the stunting of human mental life in conditions of adversity requires us to open up the black box of 'environment', and to develop a vitalist biosocial science, informed by and in conversation with the life sciences and the neurosciences. In this paper we draw on both classical and contemporary social theory to begin this task. We explore human inhabitation – how humans inhabit their 'ecological niches' – and examine a number of conceptual developments that 'deconstruct' the binary distinction between organism and environment. We argue that we must understand the neurological, ecological and social pathways and mechanisms that shape human (mental) life if we are to address the central concerns of our discipline with inequity and injustice as these are inscribed into the bodies and souls of human beings.